The decision to have an abortion from both partners' perspectives: a dyadic analysis. (2nd January 2017) - Vandamme, Joke; Buysse, Ann; Loeys, Tom; Vrancken, Carine; T'Sjoen, Guy
Abstract: Objectives: Male partners are often involved in induced abortion although they have no legal rights. It is, however, unknown how women's thoughts and feelings regarding the decision for abortion are associated with the decisional experiences of the involved male partners and vice versa. Methods: Flemish women and their involved male partners (IMP) filled out a questionnaire on abortion motives and feelings of decisiveness in the abortion centre waiting room ( N  = 106 couples). Actor Partner Interdependence Models investigated whether the decisiveness of one partner was associated with a subjective feeling of autonomy (high internal, low external abortion motivation) and decisiveness of the other partner, above and beyond the own feeling of autonomy and personal vulnerabilities for being uncertain. Results: Partner congruence in motivation and decisiveness was substantial ( r = 0.23 to 0.42), especially for cohabiting partners. The IMPs were less internally motivated for the abortion than the women but both partners reported more internal than external motives, and they both tended to feel certain. In contrast to the women, a higher subjective feeling of autonomy in the IMPs was not associated with feeling more certain. When accounting for partners' living situation, levels of uncertainty were not only associated with personal vulnerabilities for being uncertain, but were also related to the degree of uncertainty and subjective level of autonomy of the other partner. Conclusions: Partners' thoughts and feelings regarding the decision for abortion partially have an interpersonal basis and mostly run parallel despite an inherent gender difference in level and importance of decision autonomy.